2022
DOI: 10.1186/s40478-022-01475-9
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive mild TBI causes pTau aggregation in nigra without altering preexisting fibril induced Parkinson’s-like pathology burden

Abstract: Population studies have shown that traumatic brain injury (TBI) is associated with an increased risk for Parkinson’s disease (PD) and among U.S. Veterans with a history of TBI this risk is 56% higher. The most common type of TBI is mild (mTBI) and often occurs repeatedly among athletes, military personnel, and victims of domestic violence. PD is classically characterized by deficits in fine motor movement control resulting from progressive neurodegeneration of dopaminergic neurons in the substantia nigra pars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
2
2
0
Order By: Relevance
“…We have found in pre-clinical rat models of α-Syn fibril-induced PD that pTau is localized in Lewy bodies (LBs) within dopaminergic neurons. 22 Similarly, we also found pTau aggregates within dopaminergic neurons of rats that underwent repetitive mild TBI. 22 If PTP induces pTau aggregation in surviving dopaminergic neurons, it could predispose cells to development of PD-specific proteinopathy by cross-seeding aggregation of α-Syn into LBs and Lewy neurites.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…We have found in pre-clinical rat models of α-Syn fibril-induced PD that pTau is localized in Lewy bodies (LBs) within dopaminergic neurons. 22 Similarly, we also found pTau aggregates within dopaminergic neurons of rats that underwent repetitive mild TBI. 22 If PTP induces pTau aggregation in surviving dopaminergic neurons, it could predispose cells to development of PD-specific proteinopathy by cross-seeding aggregation of α-Syn into LBs and Lewy neurites.…”
Section: Discussionsupporting
confidence: 63%
“… 22 Similarly, we also found pTau aggregates within dopaminergic neurons of rats that underwent repetitive mild TBI. 22 If PTP induces pTau aggregation in surviving dopaminergic neurons, it could predispose cells to development of PD-specific proteinopathy by cross-seeding aggregation of α-Syn into LBs and Lewy neurites. Similarly, pTau-targeted therapeutics developed for Alzheimer's disease could potentially be used to limit or slow the progression of PTP to PD.…”
Section: Discussionsupporting
confidence: 63%
“…We observed that years of contact sports participation and SN neuronal loss were associated with nigral NFTs, which were nearly twice as common as LBs in individuals with parkinsonism, and that SN neuronal loss, in turn, was associated with parkinsonism. The SN is involved early in CTE and accumulates a high p-tau burden as the disease progresses, including a concomitant loss of nigral neuromelanin-containing neurons that can be noted macroscopically at autopsy, and animal modeling has likewise demonstrated nigral p-tau following RHI . These findings together indicate nigral susceptibility to damage and degeneration following head injury.…”
Section: Discussionmentioning
confidence: 91%
“…The SN is involved early in CTE and accumulates a high p-tau burden as the disease progresses, 7,8 including a concomitant loss of nigral neuromelanin-containing neurons that can be noted macroscopically at autopsy, and animal modeling has likewise demonstrated nigral p-tau following RHI. 59 These findings together indicate nigral susceptibility to damage and degeneration following head injury.…”
Section: Discussionmentioning
confidence: 93%